2020
DOI: 10.1371/journal.pone.0233087
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Iah1, a candidate gene for diet-induced fatty liver, does not affect liver lipid accumulation in mice

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a pathological condition caused by excess triglyceride deposition in the liver. The SMXA-5 severe fatty liver mouse model has been established from the SM/J and A/J strains. To explore the genetic factors involved in fatty liver development in SMXA-5 mice, we had previously performed quantitative trait locus (QTL) analysis, using (SM/J×SMXA-5)F2 intercross mice, and identified Fl1sa on chromosome 12 (centromere-53.06 Mb) as a significant QTL for fatty liver. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…A similar clinical context study was also reported by Grander et al (30), which found Metrnl expression was decreased in hepatic-and adipose tissues after BS in non-alcoholic fatty liver disease (NAFLD). Interestingly, Metrnl has been identified as a target protein with Iah1, a candidate gene for diet-induced NAFLD (133). Maybe Metrnl as one of the hepatokines play role in NAFLD progress but further investigations are needed to clarify the mechanism.…”
Section: Metrnl and Obesitymentioning
confidence: 99%
“…A similar clinical context study was also reported by Grander et al (30), which found Metrnl expression was decreased in hepatic-and adipose tissues after BS in non-alcoholic fatty liver disease (NAFLD). Interestingly, Metrnl has been identified as a target protein with Iah1, a candidate gene for diet-induced NAFLD (133). Maybe Metrnl as one of the hepatokines play role in NAFLD progress but further investigations are needed to clarify the mechanism.…”
Section: Metrnl and Obesitymentioning
confidence: 99%
“…The increase of Cd36 mRNA level in the liver is related to the increase of hepatocellular carcinoma and the accumulation of hepatic triglycerides. Therefore, the expression of Iah1 can avoid the formation of fatty liver (Masuya et al, 2020;Kobayashi et al, 2016). Aging is related to the imbalance of glucose and lipid metabolism.…”
Section: Upregulated Proteinsmentioning
confidence: 99%